2006
DOI: 10.1179/174328406x74284
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and strain rate dependence of the dynamic strain aging effect in an Al–Zn–Mg alloy

Abstract: An AA7030 alloy (Al-5 . 4Zn-1 . 2Mg) was tested for evidence of dynamic strain aging in naturally aged and peak aged condition and under varying conditions in terms of strain rate and temperature. Clear evidence in terms of strain rate sensitivity, serrated yielding (Portevin-Le Chatelier effect) and propagative plastic instabilities was observed in the naturally aged temper while the peak aged temper only showed serrated yielding. Further evidence of dynamic strain aging was the temperature and strain depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It has been shown that, assuming proportionality between ∆g and the solute concentration at the dislocation line, the strain rate dependence of ∆g will be negative [9], indicating that S can take both positive and negative values depending on the relative magnitudes of k B T and ∂∆g/∂ln ε& .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, assuming proportionality between ∆g and the solute concentration at the dislocation line, the strain rate dependence of ∆g will be negative [9], indicating that S can take both positive and negative values depending on the relative magnitudes of k B T and ∂∆g/∂ln ε& .…”
Section: Discussionmentioning
confidence: 99%
“…The NA samples were deformed with a total strain amplitude of 0.6% and the PA with 0.8%, this to yield plastic strain amplitudes of 0.2% at half-life, at temperatures of -20, 20 and 60ºC. Inspired by the results on the influence of temperature on the monotonic properties of AA7030 [1][2][3]13], it was decided to perform tests at both lower and higher temperatures than ambient, namely 20 C, 20 C and 60 C. …”
Section: Methodsmentioning
confidence: 99%
“…The alloy AA7030 has been shown earlier to exhibit strong DSA effects in naturally aged [1][2][3] and solution treated [4][5][6][7][8] conditions, while weak effects were found in the peak-aged material [1][2][3]8].…”
Section: Introductionmentioning
confidence: 99%
“…Under plastic flow, dislocations are gliding until they come across an obstacle where they are stationary until the obstacles are surmounted. When the dislocations are stationary, solute atoms can diffuse towards the dislocations which result in an increase in the activation energy for further slip and consequently also an increase in the stress needed for overcoming the obstacle [92][93][94][95][96][97]. Thus, DSA is directly influenced by the deformation rate that affects the mobility of the dislocations and the temperature that influences the diffusion rate of solute atoms.…”
Section: Dynamic Strain Ageingmentioning
confidence: 99%